Town Built On Skewers Of Meat - New Straits Times, (2008)
Whenever the name of Kajang is brought up, the respone is always 'satay!' That was true about 20 years ago. According to long-time resident of Kajang, the best Kajang satay is now found in Kuala Lumpur.